Combating capital flight from developing countries - Wilhelm Nölling (Intereconomics, 1986)
The flight of capital from the highly indebted developing countries undoubtedly constitutes one of the most serious problems that are making the international debt crisis difficult if not impossible to resolve. Dr. Nölling outlines some suggestions for action which could limit capital flight significantly in the short term.
Keywords: 330; Debt Problems